Diagnostic performance of morning basal serum cortisol for assessing adrenal reserve: a single-center experience from the United Arab Emirates - Raya Almazrouei; Jawaher Alshamsi; Mohamed Abdelsalhen; Fatima Alkaabi; Adnan Agha (Therapeutic Advances in Endocrinology and Metabolism)
Introduction: Adrenal insufficiency can be life-threatening due to the lack of cortisol elevation in times of stress. The short Synacthen test (SST) is the most common diagnostic test for adrenal insufficiency. This study aimed to assess the diagnostic performance of morning basal serum cortisol during an SST to assess normal adrenal reserve in a local Emirati population. Methods: We retrospectively analyzed the electronic medical records of adult patients who underwent morning SST to assess adrenal reserve between August 2012 and August 2022. Results: This study included 344 patients (201 women) with a mean age of 49.1 ± 22.6 years. Based on the previously published cutoff data for SST peak values at 30 min (408 nmol/L for Beckman-Access used from 2012 to 2017 and 402 nmol/L for Roche-Cobas Generation-II used since 2018) as a gold standard to identify patients with adequate adrenal reserve, 106 patients (30.8%) were diagnosed with adrenal insufficiency and 238 (69.2%) with adequate adrenal reserve. Using the receiver–operator characteristics curve for morning cortisol, we identified a cutoff of 332 nmol/L, which corresponded to adequate Synacthen stimulation with 100% specificity and 73% sensitivity. Morning cortisol levels of <96 nmol/L corresponded to suboptimal adrenal response to SST, with 95% specificity and 55% sensitivity. Conclusion: We propose that a morning cortisol cutoff of >332 nmol/L can help identify patients with adequate adrenal reserve, thereby avoiding unnecessary SSTs.